Promoting Peace and Democracy through Party Regulation? Ethnic Party Bans in Africa - Anika Becher; Matthias Basedau (German Institute of Global and Area Studies (GIGA), 2008)
Since the sweeping (re)introduction of multiparty systems in the early 1990s almost all sub-Saharan countries have introduced bans on ethnic or - in more general terms - particularistic parties. Such party bans have been neglected in research, and this paper engages in a preliminary analysis of their effects on democracy and peace. Theoretically, particularistic party bans can block particularisms from entering politics but also run the risk of forcing groups to resort to extra-legal or violent means. Neutral or context-dependent effects are also possible. Applying macro-qualitative comparison and bivariate statistics on the basis of a unique inventory of party bans and readily available indicators for the dependent variables, no simple connection can be detected. Rather, context conditions seem to be of superior explanatory power. We also find a systematic connection between party bans and variables that could be conceptualized as the causes of their implementation. – – Seit der flächendeckenden (Wieder-)Einführung von Mehrparteiensystemen zu Anfang der 1990er Jahre haben fast alle subsaharischen Länder ethnische oder - allgemeiner - partikularistische Parteien verboten. Diese Verbote wurden bislang kaum untersucht und der vorliegende Artikel unternimmt eine vorläufige Analyse ihrer Auswirkungen auf Demokratie und Frieden. Theoretisch betrachtet können durch solche Verbote ethnische oder andere Partikularismen aus dem politischen System herausgehalten werden, sie könnten entsprechende Gruppen aber möglicherweise auch zum Rückgriff auf nicht verfassungsmäßige oder gewaltsame Mittel zwingen. Neutrale oder kontextabhängige Auswirkungen sind ebenfalls denkbar. Unter Anwendung makroqualitativer Vergleiche und bivariater Statistiken auf Basis einer einzigartigen Datenbasis zu Parteienverboten in Afrika und verfügbaren Indikatoren für die abhängigen Variablen können jedoch keine einfachen Auswirkungen von Parteienverboten entdeckt werden. Kontextbedingungen scheinen von höherer Erklärungskraft. Zwar sind systematische Zusammenhänge mit Variablen erkennbar, diese können aber eher als Ursachen von Parteienverboten angesehen werden.
Keywords: 300; Sub-Saharan Africa; party bans; ethnicity; conflict; democracy